Assessing axial and temporal effects of the leaf sheath on the flexural stiffness of large‐grain stems. Issue 2 (19th February 2023) - Hale, Jared; Webb, Spencer; Hale, Nathan; Stubbs, Christopher; Cook, Douglas
Abstract: The leaf sheath of many plants has been observed to influence both stiffness and ultimate strength. For example, the sheath has been observed to be closely related to "greensnap" (or "brittle‐snap") failure of Zea mays . The goal of this study was to develop a method for assessing longitudinal and temporal patterns of sheath influence on flexural stiffness. This metric was chosen because it has been shown to be predictive of ultimate bending strength. A three‐point bending test method was developed for assessing the longitudinal and temporal influence of the sheath on flexural stiffness of Zea mays . Comparisons between pairs of tests at the same location (sheath present vs. absent) were performed. Four types of maize were tested. The sheath had a statistically significant influence on bending. Sheath influence appears to be closely related to maturity since both spatial and temporal patterns of influence mirror the sigmoidal maturation patterns previously observed in maize stalks. The paired nature of this method increases statistical significance and allows for multiple tests along the length of the stalk. Results indicate that the influence of the sheath changes over the life span of the Zea mays in parallel with maturation patterns. However, further studies will be needed to confirm this hypothesis more broadly and to study additional issues such as heritability and the influence of genotype and environment on sheath effects. Due to the common architecture of Poacea plants, this method can be used to provide new insights on sheath influences of various species. Core Ideas: Leaf sheaths provide structural support to maize stalks. Leaf sheaths influence varies spatially and temporally. A new three‐point bending test provides high spatial resolution as well as high statistical power. Leaf sheath influences mirror maturation patterns of the stalk.